EFEKTIVITAS PEMBELAJARAN PPKn BERBASIS METODE INTERAKTIF UNTUK MENINGKATKAN KESADARAN POLITIK SISWA KELAS IX FASE F - Rahma Nindi Putri; Asril; Azwar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by low student interest and participation in political issues, as well as the need for a more applicable and participatory learning approach. Interactive methods such as group discussions and election simulations are considered capable of accommodating students' needs to understand political dynamics in a more concrete and enjoyable way. This study aims to assess the effectiveness of interactive-based Pancasila and Citizenship Education (PPKn) learning in increasing the political awareness of 11th-grade Phase F students at SMA Negeri 1 Lembah Gumanti. This research used a qualitative case study approach, with data collection techniques through observation, interviews, and documentation. The results indicate that the application of interactive methods in PPKn learning has a positive impact on increasing student participation, understanding, and political awareness. Students become more active in discussions, confidently express their opinions, and are able to connect the material to political events around them. The mini-election simulation serves as an effective means of instilling democratic values, such as responsibility, honesty, and tolerance. The findings of this study indicate that interactive learning is relevant in the context of the Independent Curriculum as a strategy to shape democratic and national-minded student character. The main supporting factors for the success of this learning process are the teacher's role as a facilitator, the availability of learning resources, and active student involvement. Obstacles faced include time constraints, diverse student communication skills, and limited experience in political practice. Overall, interactive PPKn learning has proven effective in comprehensively increasing students' political awareness.